Perbandingan Pemasangan Implan Dental Single-Tooth Loss: Faktor Risiko dan Penyulit - Jessica Ratri Suryoputri; Yessy Ariesanti (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Edentulous cases or missing teeth is one of the problems complained about by patients in daily dental practice. Missing teeth are mostly discovered in adult patients, especially in posterior teeth such as premolar and molar. Nowadays, dental implant restoration in posterior single-tooth loss cases has been stated as the best treatment option. Nevertheless, hypertension is one of the risk factors that might cause difficulties in the dental implant procedure. Purpose: to compare the insertion of a dental implant in single-tooth loss between a patient without any systemic disease and a patient with a history of hypertension, using the same dental implant system and in the same timeframe. Case and Procedure: Case # 1, female patient age 43 years old came to RSGM-P FKG Usakti to have a dental implant insertion in the lower right posterior region. There was an absence of system disease in this patient. There were no difficulties during the dental implant insertion in tooth 46, therefore the osseointegration occurred nicely and the restorative crown insertion was precisely inserted. Case # 2, male patient age 49 years old with a chief complaint of missing tooth in the lower left posterior region, wanted to have a dental implant insertion. The patient had a history of hypertension with a regular daily intake of Amlodipine 5 mg once a day. Osseointegration occurred well after the dental implant insertion in tooth 35. However, during the screw uncovering stage, there was bone growth covering the surface of the cover screw. Therefore, removal of the bone growth should be done by using a round bur. In the impression-taking stage, there was slight gingival enlargement or overgrowth that almost covered the path of crown insertion. Gingivectomy had to be done before taking the impression in order to achieve precise crown insertion. The risk factor in the second case is that the patient consumed Amlodipine 5 mg daily, which causes overgrowth of bone and soft tissue surrounding the cover screw and implant fixture. Conclusion: There are differences in the outcome of the dental implant insertion in a patient without systemic disease and a patient with a history of hypertension with a daily intake of Amlodipine 5 mg medication; the factor that caused difficulties in the prosthetic stage is the presence of the alveolar bone and soft-tissue overgrowth.